Factors Influencing Patient Perception of Clinical Laboratory Services: A Cross-Sectional Study - Hidayat, Afif Wahyudi; Setianingsih, Lyliana Endang; Hutagaol, Emmelia Kristina (Chakra Brahmanda Lentera Institute, 2026)
Background: Hospital clinical laboratories are essential for diagnosis, treatment monitoring, and clinical decision-making, and increasingly contribute to hospital revenue. However, in contrast to high-income settings where laboratory service quality has been more extensively studied, there is still limited empirical evidence from low- and middle-income countries (LMICs), including Indonesia, on how structural and process-related aspects of private hospital clinical laboratory services shape patient perceptions. This study aimed to analyze factors associated with patient perceptions of clinical laboratory services. Methods: This quantitative cross-sectional study. A total of 114 consecutively recruited patients completed the Clinical Laboratory Service Perception Questionnaire (CLSPQ), a 22-item validated instrument covering education level, physical environment (laboratory room, cleanliness of rooms and toilets, waiting area comfort), service processes (waiting time, availability of tests, clarity of information), and overall perception of laboratory services. Data were analyzed using chi-square tests and multiple logistic regression to identify independent predictors of positive patient perceptions (p < 0.05). Results: In multivariable analysis, higher education level, bright and hygienic laboratory rooms, comfortable and clean waiting areas, clear information about laboratory services, very clean laboratory rooms, clean and odorless toilets, shorter waiting times, and availability of all required laboratory tests were independently associated with positive patient perceptions of clinical laboratory services (all p < 0.001). Laboratory cleanliness showed the strongest association with positive perceptions, followed by toilet cleanliness and shorter waiting times. Conclusion: Physical environmental conditions and key service delivery processes are major determinants of how patients perceive clinical laboratory services in this LMIC private hospital. Prioritizing low-cost improvements in cleanliness, waiting room comfort, queue management, and clarity of information within continuous quality improvement programmes may substantially enhance patient satisfaction and strengthen the professional image of hospital laboratories in similar resource-limited settings.